Identificação de bactérias láticas isoladas do ecossistema mamário bovino e caracterização de seu potencial inibidor contra patógenos associados à mastite - Bianca Seridan de Assis (2015)
Mastitis causes huge economic losses in the dairy sector both in Brazil and France. They also are the first cause of antibiotic consomption in the dairy farms. There is thus a need for new alternatives to antibiotics to control infectious mastitis. In this thesis work, we isolated 278 (165 in France and 113 in Brazil) bacterial strains from bovine milk and teat canal, and identified 10 non-redundant lactic acid bacteria (LAB) strains that were further tested as potential mammary probiotic candidates. LAB strains were tested for their surface properties and production of inhibitory compounds and then evaluated for their interactions with Staphylococcus aureus and Escherichia coli, two major mastitis pathogens, or with bovine mammary epithelial cells (bMEC), in vitro. Some LAB strains (Lactobacillus brevis e Lactobacillus plantarum) presented inhibitory capacity against S. aureus adhesion and internalisation and were shown to stimulate the production of pro- and anti-inflammatory cytokines in bMEC. Other interaction tests with bMEC showed that Lactococcus lactis V7 was able to significantly inhibit bMEC invasion by Escherichia coli and S. aureus. Although the inhibitory mechanism was not elucidated, Lactococcus lactis V7 showed promising capacities in terms of mammary probiotic potential with, notably, the ability to modulate the immune response of E. coli-infected bMEC by modifying the expression of inflammatory cytokine genes. In this work, several LAB strains were identified in the milk and teat canal microbiota. We showed that L. brevis, L. plantarum and Lactococcus lactis V7 strains had interesting properties for a possible strategy to prevent or treat against mastitis.